Water-based antibacterial coating for building wall surface and preparation method of water-based antibacterial coating
By preparing an aqueous antibacterial coating containing composite nanomaterials, the problem that existing coatings cannot adapt to different substrates and lack antibacterial properties is solved, high binding force and excellent antibacterial properties are achieved, and the service life of the coating is extended.
Patent Information
- Application Number
- CN202510363506.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-05-27
- Estimated Expiration
- 2045-03-26
AI Technical Summary
Existing building exterior wall coatings cannot adapt to different substrates and lack antibacterial properties, resulting in a significant reduction in life.
Aqueous antibacterial coatings are used, which contain acrylic emulsions, film forming additives, titanium dioxide, mica powder, defoaming agents, thickening agents, dispersants, composite nanomaterials and deionized water. The bonding strength and antibacterial properties of the coating are enhanced by the preparation method of composite nanomaterials.
It improves the bonding force between the paint and the building wall, enhances antibacterial properties, can adapt to a variety of different substrates, and extends the service life of the paint.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coatings, and specifically relates to an aqueous antibacterial coating for building walls and a preparation method thereof. Background Art
[0002] Building exterior wall coatings are coatings used to protect and decorate building exterior walls. By forming a coating layer on the surface of the building exterior wall, the needs for protecting the building exterior wall under different climate and environmental conditions can be met. It can not only improve the overall quality of the building, but also effectively extend the service life of the building.
[0003] In the prior art, the application number is: CN 105949945 A, a building exterior wall coating. The present invention discloses a building exterior wall coating, which is composed of three components A, B, and C, and is mixed in a weight ratio of 3:1:1 before use. Component A is composed of epoxy resin, xylene, benzyl alcohol, and dibutyl phthalate. Component B is composed of epoxy curing agent, xylene, benzyl alcohol, dibutyl phthalate, and silane coupling agent. Component C is composed of talcum powder with a mesh size of 600 - 800 and quartz sand with a mesh size of 70 - 140. The present invention solves the problem of difficult surface renovation of existing aluminum-plastic panels, has extremely strong adhesion to the smooth surface of aluminum-plastic panels, and at the same time, the putty layer can achieve good adhesion on this product. The construction is simple and easy, and both roller coating and brush coating can be used. However, it cannot adapt to different building exterior wall substrates and does not have antibacterial properties, which easily causes a significant reduction in its lifespan.
[0004] Based on this, we propose an aqueous antibacterial coating for building walls, hoping to solve the deficiencies in the prior art. Summary of the Invention
[0005] Aiming at the deficiencies of the prior art, the present invention provides an aqueous antibacterial coating for building walls and a preparation method thereof.
[0006] To achieve the above objectives, the present invention provides the following technical solutions: An aqueous antibacterial coating for building walls, characterized in that it is made of the following components: 40 - 55 parts of acrylic emulsion, 3 - 3.8 parts of film-forming auxiliary agent, 5 - 6 parts of titanium dioxide, 2 - 3 parts of mica powder, 1 - 1.5 parts of defoaming agent, 1.2 - 1.4 parts of thickening agent, 1 - 1.2 parts of dispersing agent, 4 - 6 parts of composite nano material, 10 - 12 parts of deionized water.
[0007] As a further technical solution: The preparation method of the composite nano material is as follows: First, glacial acetic acid and absolute ethanol are sequentially added to the reaction kettle, and then tetrabutyl titanate is added dropwise, and stirring and mixing are continued for 20 min; The carbon nanotubes are uniformly dispersed in the ethanol solution to obtain a carbon nanotube dispersion. Add the carbon nanotube dispersion to the reaction kettle, adjust the temperature to 60 °C, keep warm and stir for 2 hours. After standing for 20 hours, dry it until the water content is lower than 10% to obtain the reaction material; Calcine the reaction material for 1.5 hours to obtain the first base material; The calcination temperature is 350 °C; Add zinc nitrate and potassium hydroxide to water respectively to prepare a zinc nitrate solution and a potassium hydroxide solution; The concentrations of both the zinc nitrate solution and the potassium hydroxide solution are 0.3 mol / L; Add cetyltrimethylammonium bromide to the potassium hydroxide solution, stir for 10 min, then heat to 75 °C, add the zinc nitrate solution, continue to stir for 2 hours, stand for 2 hours, and after suction filtration and drying, obtain the second base material; The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; Mix the second base material and the first base material evenly to obtain the composite nano material; The second base material and the first base material are mixed in a mass ratio of 10:1 - 2.
[0008] As a further technical solution: Among them, the volume ratio of glacial acetic acid to absolute ethanol is 1:3; The volume ratio of glacial acetic acid to tetrabutyl titanate is 1.2:1; The mass fraction of the ethanol solution is 70%; The mixing ratio of carbon nanotubes to the ethanol solution is 1 - 2 g:100 mL.
[0009] As a further technical solution: The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; The second base material and the first base material are mixed in a mass ratio of 10:1 - 2.
[0010] As a further technical solution: The film-forming aid is propylene glycol.
[0011] As a further technical solution: The defoaming agent is an organosilicon defoaming agent.
[0012] As a further technical solution: The thickening agent is sodium carboxymethylcellulose.
[0013] As a further technical solution: The dispersant is sodium silicate.
[0014] A preparation method of an aqueous antibacterial coating for building walls, comprising the following steps: (1)Weigh according to each part by weight: acrylic emulsion, film-forming aid, titanium dioxide, mica powder, defoaming agent, thickener, dispersant, composite nano-material, deionized water; (2)Add the above components to a mixer in sequence and stir and mix for 30 min to obtain a preliminary mixture; (3)Perform ultrasonic dispersion on the preliminary mixture for 10 min to obtain an aqueous antibacterial coating for building walls.
[0015] Compared with the prior art, the present invention provides an aqueous antibacterial coating for building walls, having the following beneficial effects: The aqueous antibacterial coating for building walls prepared by the present invention can not only form a dense and uniform coating on the surface of the building wall, but also form a tight bond with the building wall, greatly improving the bonding force between the two. At the same time, the coating prepared by the present invention also has excellent antibacterial properties.
[0016] The composite nano-material introduced in the present invention has such a small size that the nano-particles have extremely high specific surface area and surface energy, thereby enhancing their interaction ability with other substances in the coating and forming a more stable coating system. Due to the small size of the composite nano-material, the proportion of surface atoms is large, resulting in insufficient coordination number of surface atoms, and there are a large number of unsaturated bonds and dangling bonds. These unsaturated bonds and dangling bonds are prone to chemical bonding or physical adsorption with other substances in the coating, thus greatly improving the bonding strength of the coating.
[0017] After adding the composite nano-material to the coating prepared by the present invention, the composite nano-material will form an organic-inorganic material complex with other components in the coating; and the formation of these complexes helps to enhance the internal interaction force of the coating, thereby improving the overall bonding strength of the coating. By adding the composite nano-material, the microstructure of the coating can be improved. The composite nano-material can fill the pores and defects in the coating, reduce the stress concentration points inside the coating, thereby improving the density and uniformity of the coating. At the same time, the composite nano-material can also increase the contact area and interaction points between the coating and the substrate, further enhancing the bonding strength of the coating and being able to adapt to a variety of different exterior wall material substrates.
[0018] Under the irradiation of sunlight, especially ultraviolet light, the composite nano-material can spontaneously decompose into negatively charged electrons (e-) and positively charged holes (h+), forming electron-hole pairs; these electrons and holes will migrate to the surface of the coating, where the electrons are captured by oxygen adsorbed and dissolved on the surface of the composite nano-material to form active superoxide anion radicals; while the holes oxidize OH- and H adsorbed on their surface 2 O into hydroxyl radicals; the active oxygen and hydroxyl radicals have high reaction activity and can undergo oxidation reactions with a variety of microorganisms, thereby destroying the cell structure of bacteria and achieving the effect of sterilization. Detailed implementation manners
[0019] Next, in combination with the embodiments of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0020] Acrylic emulsion with a solid content of 45%; Embodiment
[0021] A preparation method of an aqueous antibacterial coating for building walls, comprising the following steps: (1) Weigh according to each weight part: 40 parts of acrylic emulsion, 3 parts of propylene glycol, 5 parts of titanium dioxide, 2 parts of mica powder, 1 part of silicone defoamer, 1.2 parts of sodium carboxymethyl cellulose, 1 part of sodium silicate, 4 parts of composite nano-material, and 10 parts of deionized water.
[0022] The preparation method of the composite nano-material is as follows: First, add glacial acetic acid and absolute ethanol to the reaction kettle in sequence, then dropwise add tetrabutyl titanate, and continue to stir and mix for 20 min; Uniformly disperse carbon nanotubes in an ethanol solution to obtain a carbon nanotube dispersion; Add the carbon nanotube dispersion to the reaction kettle, adjust the temperature to 60 °C, keep warm and stir for 2 hours, stand for 20 hours, and then dry until the moisture content is lower than 10% to obtain a reaction material; Calcine the reaction material for 1.5 hours to obtain a first base material; The calcination temperature is 350 °C; Add zinc nitrate and potassium hydroxide to water respectively to prepare a zinc nitrate solution and a potassium hydroxide solution; The concentrations of the zinc nitrate solution and the potassium hydroxide solution are both 0.3 mol / L; Add cetyltrimethylammonium bromide to the potassium hydroxide solution, stir for 10 min, then heat to 75 °C, add the zinc nitrate solution, continue to stir for 2 hours, stand for 2 hours, and after filtration and drying, obtain a second base material; The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; Mix the second base material and the first base material evenly to obtain a composite nano-material; The second base material and the first base material are mixed in a mass ratio of 10:1.
[0023] Among them, the volume ratio of the glacial acetic acid to the absolute ethanol is 1:3; The volume ratio of glacial acetic acid to tetrabutyl titanate is 1.2:1; The mass fraction of the ethanol solution is 70%; The mixing ratio of carbon nanotubes to the ethanol solution is 1 g: 100 mL.
[0024] The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; The second base material and the first base material are mixed in a mass ratio of 10:1; (2) Add the above components to a mixer in sequence, stir and mix for 30 min to obtain a preliminary mixture; (3) Perform ultrasonic dispersion on the preliminary mixture for 10 min to obtain an aqueous antibacterial coating for building walls. Example
[0025] A preparation method of an aqueous antibacterial coating for building walls includes the following steps: (1) Weigh according to each weight part: 50 parts of acrylic emulsion, 3.5 parts of propylene glycol, 5.2 parts of titanium dioxide, 2.8 parts of mica powder, 1.4 parts of silicone defoamer, 1.3 parts of sodium carboxymethyl cellulose, 1.1 parts of sodium silicate, 5 parts of composite nano material, and 11 parts of deionized water.
[0026] The preparation method of the composite nano material is as follows: First, add glacial acetic acid and absolute ethanol to a reaction kettle in sequence, then dropwise add tetrabutyl titanate, and continue to stir and mix for 20 min; Disperse carbon nanotubes evenly in the ethanol solution to obtain a carbon nanotube dispersion; Add the carbon nanotube dispersion to the reaction kettle, adjust the temperature to 60 °C, keep warm and stir for 2 hours, let it stand for 20 hours, and then dry until the moisture content is lower than 10% to obtain a reaction material; Calcine the reaction material for 1.5 hours to obtain a first base material; The calcination temperature is 350 °C; Add zinc nitrate and potassium hydroxide to water respectively to prepare a zinc nitrate solution and a potassium hydroxide solution; The concentrations of both the zinc nitrate solution and the potassium hydroxide solution are 0.3 mol / L; Add cetyltrimethylammonium bromide to the potassium hydroxide solution, stir for 10 min, then heat to 75 °C, add the zinc nitrate solution, continue to stir for 2 hours, let it stand for 2 hours, and after suction filtration and drying, obtain a second base material; The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; Mix the second base material and the first base material evenly to obtain a composite nano material; The second base material and the first base material are mixed in a mass ratio of 10:1.5.
[0027] Among them, the volume ratio of the glacial acetic acid to the absolute ethanol is 1:3; The volume ratio of the glacial acetic acid to the tetrabutyl titanate is 1.2:1; The mass fraction of the ethanol solution is 70%; The mixing ratio of the carbon nanotubes to the ethanol solution is 1.2 g:100 mL.
[0028] The addition amount of the cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; The second base material and the first base material are mixed in a mass ratio of 10:1.5; (2) Add the above components to a mixer in sequence, stir and mix for 30 min to obtain a preliminary mixture; (3) Perform ultrasonic dispersion on the preliminary mixture for 10 min to obtain an aqueous antibacterial coating for building walls. Example
[0029] A preparation method of an aqueous antibacterial coating for building walls includes the following steps: (1) Weigh according to each weight part: 55 parts of acrylic emulsion, 3.8 parts of propylene glycol, 6 parts of titanium dioxide, 3 parts of mica powder, 1.5 parts of silicone defoamer, 1.4 parts of sodium carboxymethyl cellulose, 1.2 parts of sodium silicate, 6 parts of composite nano material, and 12 parts of deionized water.
[0030] The preparation method of the composite nano material is as follows: First, add glacial acetic acid and absolute ethanol to the reaction kettle in sequence, then dropwise add tetrabutyl titanate, and continue to stir and mix for 20 min; Disperse the carbon nanotubes evenly in the ethanol solution to obtain a carbon nanotube dispersion; Add the carbon nanotube dispersion to the reaction kettle, adjust the temperature to 60 °C, keep stirring for 2 hours, let it stand for 20 hours, and then dry it until the moisture content is lower than 10% to obtain a reaction material; Calcine the reaction material for 1.5 hours to obtain the first base material; The calcination temperature is 350 °C; Add zinc nitrate and potassium hydroxide to water respectively to prepare a zinc nitrate solution and a potassium hydroxide solution; The concentrations of both the zinc nitrate solution and the potassium hydroxide solution are 0.3 mol / L; Add cetyltrimethylammonium bromide to the potassium hydroxide solution, stir for 10 min, then heat to 75 °C, add the zinc nitrate solution, continue to stir for 2 hours, let stand for 2 hours, and obtain the second base material after suction filtration and drying; The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; Mix the second base material and the first base material evenly to obtain the composite nano material; The second base material and the first base material are mixed in a mass ratio of 10:2.
[0031] Among them, the volume ratio of the glacial acetic acid to the absolute ethanol is 1:3; The volume ratio of the glacial acetic acid to the tetrabutyl titanate is 1.2:1; The mass fraction of the ethanol solution is 70%; The mixing ratio of the carbon nanotubes to the ethanol solution is 2 g:100 mL.
[0032] The addition amount of cetyltrimethylammonium bromide is 1.5 wt%; The addition amount of the zinc nitrate solution is added according to the molar ratio of zinc nitrate to potassium hydroxide of 1:2; The second base material and the first base material are mixed in a mass ratio of 10:2; (2) Add the above components to the mixer in sequence, and stir and mix for 30 min to obtain the preliminary mixture; (3) Perform ultrasonic dispersion on the preliminary mixture for 10 min to obtain the waterborne antibacterial coating for building walls.
[0033] The following are comparative examples: Comparative Example 1: On the basis of Example 1, the composite nano material is not added, and the other technical solutions are the same as those of Example 1.
[0034] Comparative Example 2: On the basis of Example 1, the composite nano material is only replaced with an equal amount of the first base material, and the other technical solutions are the same as those of Example 1.
[0035] Comparative Example 3: On the basis of Example 1, the composite nano material is only replaced with an equal amount of the second base material, and the other technical solutions are the same as those of Example 1.
[0036] Test: Use the draw method to test the bonding strength of the coatings of the examples and comparative examples on three different substrates: cement substrate, non-flat ceramic tile surface, and flat glazed ceramic tile surface. The detection method refers to JC / 2090-2011; Table 1 Cement substrate
[0037] As can be seen from Table 1, the coating prepared by the present invention has excellent bonding properties to cement substrates; Table 2 Smooth glazed tile surface
[0038] As can be seen from Table 2, the coating prepared by the present invention has relatively high bonding properties to the smooth glazed tile surface.
[0039] Table 3 Non-smooth tile surface
[0040] As can be seen from Table 3, the coating prepared by the present invention has relatively high bonding strength to the non-smooth tile surface.
[0041] The antibacterial properties of the samples of the examples and comparative examples were tested. After coating and drying to form a coating with a thickness difference of no more than 0.1 mm, the test was carried out with reference to "GB / T 21866-2008 Determination method for antibacterial properties and antibacterial effect of antibacterial coatings". The selected bacteria were Staphylococcus aureus and Escherichia coli; Table 4
[0042] As can be seen from Table 4, the coating prepared by the present invention has excellent antibacterial properties.
[0043] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A water-based antibacterial coating for building walls, characterized in that: The composition comprises the following ingredients by weight: 40-55 parts of acrylic emulsion, 3-3.8 parts of film-forming aid, 5-6 parts of titanium dioxide, 2-3 parts of mica powder, 1-1.5 parts of defoaming agent, 1.2-1.4 parts of thickener, 1-1.2 parts of dispersant, 4-6 parts of composite nanomaterial, and 10-12 parts of deionized water.
2. The water-based antibacterial coating for building walls according to claim 1, characterized in that: The composite nanomaterial preparation method is: First, glacial acetic acid and anhydrous ethanol were added to the reactor in sequence, and then butyl titanate was added dropwise, and the mixture was stirred and mixed for 20 minutes; uniformly dispersing the carbon nanotubes in an ethanol solution to obtain a carbon nanotube dispersion; Add the carbon nanotube dispersion into the reaction kettle, adjust the temperature to 60°C, keep warm and stir for 2 hours, let it stand for 20 hours, and then dry it until the moisture content is less than 10% to obtain a reaction material; The reaction material is calcined for 1.5 hours to obtain a first base material; The calcination temperature is 350°C; Add zinc nitrate and potassium hydroxide to water to prepare zinc nitrate solution and potassium hydroxide solution respectively; The concentrations of zinc nitrate solution and potassium hydroxide solution are both 0.3 mol / L; Add hexadecyltrimethylammonium bromide to the potassium hydroxide solution, stir for 10 minutes, heat to 75°C, add zinc nitrate solution, continue stirring for 2 hours, let stand for 2 hours, filter and dry to obtain a second base material; The amount of hexadecyltrimethylammonium bromide added was 1.5wt%; The zinc nitrate solution is added in a molar ratio of zinc nitrate to potassium hydroxide of 1:2; The second base material is mixed evenly with the first base material to obtain a composite nanomaterial; The second base material is mixed with the first base material in a mass ratio of 10:1-2.
3. A water-based antibacterial coating for building walls according to claim 2, characterized in that: The volume ratio of the glacial acetic acid to anhydrous ethanol is 1:3; The volume ratio of glacial acetic acid to butyl titanate is 1.2:1; The mass fraction of ethanol solution is 70%; The mixing ratio of carbon nanotubes and ethanol solution is 1-2g:100mL.
4. The water-based antibacterial coating for building walls according to claim 3, characterized in that: The amount of hexadecyltrimethylammonium bromide added is 1.5wt%; The zinc nitrate solution is added in a molar ratio of zinc nitrate to potassium hydroxide of 1:2; The second base material is mixed with the first base material in a mass ratio of 10:1-2.
5. The water-based antibacterial coating for building walls according to claim 1, characterized in that: The film-forming aid is propylene glycol.
6. The water-based antibacterial coating for building walls according to claim 1, characterized in that: The defoamer is an organosilicon defoamer.
7. The water-based antibacterial coating for building walls according to claim 1, characterized in that: The thickener is sodium hydroxymethyl cellulose.
8. The water-based antibacterial coating for building walls according to claim 1, characterized in that: The dispersant is sodium silicate.
9. A method for preparing a water-based antibacterial coating for building walls according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh the following according to weight: acrylic emulsion, film-forming aid, titanium dioxide, mica powder, defoamer, thickener, dispersant, composite nanomaterial, and deionized water; (2) Add the above components into a mixer in sequence and stir and mix for 30 minutes to obtain a preliminary mixture; (3) The preliminary mixture is ultrasonically dispersed for 10 minutes to obtain a water-based antibacterial coating for building walls.
Citation Information
Patent Citations
Exterior wall coating for building
CN105949945A
Lithium titanate microsphere / carbon nanotube composite material and preparation method thereof
CN108878845A
Environmentally-friendly building wall surface aqueous antibacterial coating material and preparation method thereof
CN110256916A
Method for preparing exterior wall coating for building from dispersant-modified multi-walled carbon nanotubes
CN110698928A
Nano antibacterial gel material and preparation method thereof
CN112494714A